The Effect of Capital Structure on Firm Performance in the South African Banking Sector over the Past Decade - Patel, Shazia; Brijlal, Pradeep (International Journal of Economics and Financial Issues, 2026)
This paper examines the relationship between capital structure and firm performance, specifically focusing on 13 major South African banks within the Financial 15 (FINI 15) Index between 2013 and 2022. The objectives include analyzing capital structure dynamics using debt-to-equity ratios, examining the relationship between capital structure indicators of long-term debt, short-term debt, and total debt and firm accounting performance metrics of return on equity (ROE) and return on assets (ROA), and interpreting the results through prominent capital structure theories, including the trade-off and pecking order theories. The key results show no statistically significant relationship between capital structure indicators and profitability metrics, suggesting factors beyond leverage policy drive performance. The research is significant for providing empirical evidence on major South African banks and for addressing a gap in the literature. The results offer practical implications for bank executives, policymakers, shareholders, and investors when evaluating financing decisions and performance objectives.